Investigation of the effects of lights, temperatures and packaging materials on the virgin rapeseed oil flavors during storage. (1st March 2022) - Wang, Mengzhu; Wang, Mengmeng; Huyan, Zongyao; Li, Qi; Hu, Keqing; Li, Jinwei; Yu, Xiuzhu
Abstract: How external factors affect virgin rapeseed oil (VRO) flavor was explored from the perspective of key flavor-related compounds (KFCs). Light (sunlight, ultraviolet light, and dark), temperature (ambient temperature and 60 °C), and packaging materials (glass and plastics) were selected. Induction periods (IPs) of samples in packaging materials and surface hydrophilicity of the materials were measured. The results showed that aldehydes increased from 3.654 to 10.183 to 82.762–262.580 and 10.147–50.076 mg/kg under 60 °C and ultraviolet light, respectively, in six VROs. At 60 °C, alkenals were only detected at about 60–100 meq/kg, while nitriles, pyrazines, and isothiocyanates could not be detected at the end. Compared with those in polyethylene terephthalate (203.5–452.0 min), and polypropylene (207.0–458.5 min) plastic bottles, VROs samples in glass bottles showed longer IPs (226.0–486.0 min) representing better oxidation stability as well as flavor preservation during storage ( p < 0.05). Glass was determined enhanced hydrophilicity with contact angle of 44.53° compared with polyethylene terephthalate (59.80°), and polypropylene (77.10°) plastic that promoted combination with polar KFCs and other compounds, which was helpful for increasing surface tension at oil/air interface with restricted oxygen diffusion to reduce oxidation rate, and preventing volatilization of KFCs. Highlights: Alkenals emerge at late oxidation at 60 °C with higher energy input for oxidation. KFCs should be prevented from light and high temperature. Glass with enhanced surface hydrophilicity slowed oil oxidation. Glass coupled with KFCs better to reduce volatilization and preserve flavor.